Winter-catastrophies in the reindeer husbandry of Finland: Losses and their prevention - Helle, Timo; Säntti, V. (Rangifer, 1982)
The paper deals with the occurreance of disastrous winters to the reindeer industry in Finland with special attention on the winter catastrophies and tje condition of the pastures, the influence of the disasters upon the population dynamic of the reindeer and the methods used to prevent catastrophies. A reindeer catastrophy has been defined as a situation where the number of reindeer stays 20% below the mean of the reindeer numbers during the two preceeding years. During the winter-catastrophies from 1970/71 to 1980/81 4.5% of the total reindeer number was lost. The highest losses were found in the northwesternmost part of Lappland, where there is no alternative to the reindeer lichen as it is in the middle and southern part of the reindeer industry area (arboreal lichens and supplemental feeding). In Kaldoaivi reindeer association (district), which has been studied in detail, the calf percentage is depending upon how the reindeer is able to manage the winter (r=0.62, n=ll, p«0.05). There is also a positive correlation between the slaughterweight of the calves in the early winter and the calf rate (r=0.79, n=7, p«0.05).During severe winters the mortality rate of males exceeds that of the females. Winter-catastrophies may be prevented by deminishing the numer of reindeer and by guiding the harvest to the most risky cohorts of the population. It has been proved that supplementary and emergency feeding are the most effective methods. In a normal year during the 1970s the total use of dry hay was 0.5—1.5 mill, kg., being up to 5.9—12.5 kg. per reindeer/year. In normal winters 10—16% of the total reindeer stock was intensively fed in enclosures. Supplementary feeding in enclosures is most common in the middle and southern parts of the reindeer industry area, where the essential feed is grown on own land. Katotalvet suomen poronhoidossa: menetykset ja Niiden Torjunta. Abstract in Finnish / Yhteenveto: Artikkeli käsittelee katastrofitalvien esiintymistå Suomen poronhoidossa. Erityistä huomiota kiinnitetään talvikatojen ja laiduntilanteen välisiin yhteyksiin, katojen vaikutuksiin poron populaatiodynamiikkaan sekå käytettyihin katojen ennalta ehkåisymenetelmiin. Porokato on määritetty tilanteeksi, jossa porojen määrä (yli 1-vuotiaat ja vasat) jåå 20% pienemmäksi kuin kahden edellisen vuoden porolukujen keskiarvio. Poronhoitovuosina 1970/71—1980/81 talvikadoissa menetettiin 4.5% kokonaisporomäärästä. Mentykset olivat suurimmat pohjoisimmassa Lapissa, missa porojen saatavilla ei ole jäkälän kaivun estyesså vaihtoehtoista ravintoa kuten poronhoitoalueen etelå- ja keskiosissa. Lähemmin tarkastelluss a Kaldoaivin paliskunnassa Utsjoella vasaprosentti on riippuvainen siitå, miten hyvin porot ovat selvinneet talvesta (r=0.62, n=ll, p«0.05). Vasojen syystalvisen teuraspainon ja vasaprosentin välillä on myös positiivinen korrelaatio (r=0.79, n=7, p«0.05). Vaikeina talvina hirvaiden kuolevuus on suhteellisesti suurempi kuin vaadinten. Talvikatastrofeja voidaan ehkåistå ennakolta porolukua alentamalla (varsin harvinaista) ja kohdistamalla teurastus populaation riskialteimpaan osaan. Tehokkaimmaksi osoittautunut menetelmå on kuitenkin lisä-ja hätäruokinnan järjestäminen. Normaalivuosina lisäruokintaan käytettiin 1970-luvulla 0.5—1.5 milj. kg kuiva heinää, ts. 5.9—12.5 kg yli 1-vuotiasta poroa kohti. Intensiivisessä tarharuokinnassa elätettiin normaalitalvina 10—16% porokannasta. Lisäruokinta ja tarhaus on yleisintä poronhoitoalueen etelä- ja keskiosissa, missä tarvittava rehu on saatavissa omasta takaa. Vinterkatastrofer inom renskötseln i Finland: Förluster och deras förebyggande. Abstract in Swedish / Sammandrag: Artikeln behandlar forekomsten av katastrofvintrar inom renskötsen i Finland. Sårskilt uppmärksamhet fästs vid sambandet mellan vinterkatastrofer och betesmarkernas Situation, katastrofernas inverknan på renens populationsdynamik samt de metoder som används fôr att forebygga katastrofer. En renkatastrof har definierats som en Situation, dar antalet av renar (över 1-åriga och kalvar) stannar 20% under genomsnittet av de två foregående årens renantal. I vinterkatastroferna under renskotselåren 1970/71 — 1980/81 förlorades 4.5% av det totala renantalet. Förlusterna var störst i nordligaste Lappland, dar det inte finns alternativ föda till renlaven (hänglav och tillskottsutfodring), såsom i renskotselområdets södra och mellersta delar. I Kaldoaivi renbeteslag i Utsjoki, som granskas närmare, är kalvprocenten beroende av hur val renarna klarar sig över vintern (r=0.62, n=ll, p«0.05). Mellan kalvarnas slaktvikt på förvintern och kalvprocenten forekommer också en positiv korrelation (r=0.79, n=7, p«0.05). Under svåra vintrar är hanrenarnas dödlighet relativt sett större an honrenarnas. Vinterkatastrofer kan forebyggas genom att minska renantalet och genom att inrikta slakten på populationens mest riskfyllda del. Det har visat sig att den mest effektiva metoden är tillskotts- och nödutfodring. Under normalår användes under 1970-talet till tillskottsutfodring 0.5—1.5 miljoner kg torrt hö, d.v.s. 5.9—12.5 kg per ren över ett år. Med intensiv utfodring i inhägnader skotte man under normala vintrar 10—16% av renstammen. Tilskottsutfodring och skötsel i inhågner år vanligast i renskotselområdets södra och mellersta delar, dår man kan få det nödvändiga fodret från egna marker.